2013
DOI: 10.4081/gh.2013.67
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of the progression of Aujeszky’s disease virus infection in wild boar of Saxony-Anhalt, Germany

Abstract: Abstract. Aujeszky's disease (AD, pseudorabies) is a notifiable disease caused by Suid herpesvirus 1 (SuHV-1), also named pseudorabies virus (PrV). The study aimed at determining the occurrence and spatio-temporal trend of specific antibodies to AD virus (ADV) among wild boar of Saxony-Anhalt, a landlocked federal state situated in the western part of eastern Germany. To this end, a total of 7,209 blood samples were collected and tested from 2000 to 2011. An average seroprevalence of 6.8% was found for the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…While previous approaches to assess PRV seroprevalence in wild boar populations of Germany mainly focused on East Germany [22,[24][25][26] and only occasionally targeted regions in other parts of the country [21,[27][28][29], this study represents the first nationwide monitoring of PRV infection in wild boars. Unfortunately, for reasons mentioned above, the monitoring was spatially and temporally incomplete (Table 1, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous approaches to assess PRV seroprevalence in wild boar populations of Germany mainly focused on East Germany [22,[24][25][26] and only occasionally targeted regions in other parts of the country [21,[27][28][29], this study represents the first nationwide monitoring of PRV infection in wild boars. Unfortunately, for reasons mentioned above, the monitoring was spatially and temporally incomplete (Table 1, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Even for the Eastern parts of Germany, it has been suggested that the increase in PRV seroprevalence over a 24 year observation period (1985-2008) is a consequence of strong disease dynamics, which may have led to a westward spread at an average speed of 3.3 km/year [25,26,60]. However, phylogenetic evidence suggests at least two different PRV variants are circulating in wild boar populations in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest seroprevalences have been documented in Mediterranean countries including Spain (up to 100 %) [ 1 , 17 , 34 – 39 ], Italy (up to 51 %) [ 40 , 41 ] and Croatia (up to 57 %) [ 42 , 43 ], as well as in Romania (55 %) [ 44 ]; followed by central and eastern European countries such as Slovenia (31 %) [ 45 , 46 ], Austria (38 %) [ 47 ], Czech Republic (30 %) [ 48 ] and northeastern Germany (up to 29 %) [ 19 , 49 ]. In contrast, there is an area with low to moderate ADV seroprevalences in the centre and north of Europe: Switzerland (<4 %) [ 31 , 50 ], the Netherlands (0 %) [ 51 – 53 ], Sweden (0 %) [ 33 , 54 – 58 ], parts of France [ 13 , 59 – 61 ] and of Germany [ 19 , 49 , 62 64 ]. Within this area of low seroprevalences, multiple regions with higher seroprevalences exist: Although the overall seroprevalence of continental France lies at 6 %, several provinces in the centre (Le Loir-et-Cher, le Loiret), in the northwest (l’Ille-et-Villaine), in the Mediterranean area (Corse) and the north-east of France (les Ardennes, la Meuthe-et-Moselle, la Meuse) reach levels between 21 and 54 % [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Identification of significant disease clusters can also advance our understanding of a disease in several ways including suggesting potential risk factors for further investigation either directly (Calistri et al, 2013;French et al, 2005;Sinkala et al, 2014;Kelen et al, 2012;Nogareda et al, 2013;Poljak et al, 2007;Le et al, 2012;Vigre et al, 2005;Ward and Carpenter, 2000), or indirectly when analysis of model residuals indicates the modelled predictors do not explain fully the spatial heterogeneity in disease distribution (Méroc et al, 2014;Borba et al, 2013), or by defining the scale of disease clustering (French et al, 2005;Le et al, 2012;French et al, 1999;Wilesmith et al, 2003;Picado et al, 2007;Picado et al, 2011;Porphyre et al, 2007;Sanchez et al, 2005;Minh et al, 2010;Xu et al, 2012;Métras et al, 2012;Abatih and Ersbøll, 2009) and thereby indicate likely transmission mechanisms involved in disease spread (Sinkala et al, 2014;Ward et al, 2013;Loobuyck et al, 2009;Ohlson et al, 2014;Rosendal et al, 2014;Poljak et al, 2010). Cluster detection can also be used identify areas where vectors and hosts coincide resulting in potentially increased risk of disease transmission (Shaman, 2007;Hennebelle et al, 2013;Swirski et al, 2007), highlight possible regional differences in disease transmission (Kelen et al, 2012), or track the direction and geographical extent of disease spread (Wilesmith et al, 2003;Denzin et al, 2013;…”
Section: Cluster Detectionmentioning
confidence: 99%